Amphibian declines : the conservation status of United States species - Lannoo, Michael J. (University of California Press, 2005)
Comprehensive coverage of environmental degradation in the US as seen through the lens of amphibian ecologies. Over recent decades a massive decline has been sustained by many amphibian species, an indication of serious problems that are only now beginning to be properly appreciated.